Biochemical characterization and mycorrhizal fungal community of plant species in the Brazilian seasonal dry forest - de Souza, Tancredo Augusto Feitosa; de Lucena, Edjane Oliveira; Nascimento, Gislaine Dos Santos; da Silva, Lucas Jónatan Rodrigues [UNESP] (Wiley, 2023)
Invasive alien plant species (IAPS) have the ability to change the biochemical properties and the arbuscular mycorrhizal fungal (AMF) community structure in their rhizosphere. Organic acids, microbial activity, and AMF play a key role in the invader's spread and also has interactions with the soil chemical factors. Our aim here was to assess the rhizosphere's biochemical factors, AMF community composition, and soil chemical properties associated with Cryptostegia madagascariensis (IAPS) and Mimosa tenuiflora (endemic plant species) from the Brazilian Seasonal Dry Forest. The highest values of total glomalin (5.87 mg g-1 soil), root colonization (54.5%), oxalic and malic acids (84.21 and 3.01 μmol g-1 , respectively), microbial biomass C (mg kg-1 ), Na+ (0.080 cmolc  kg-1 ), Ca2+ (7.04 cmolc  kg-1 ), and soil organic carbon (4.59 g kg-1 ) were found in the rhizosphere of C. madagascariensis. We found dissimilarities on AMF community structure considering the studied plant species: (i) Racocetra coralloidea, Dentiscutata heterogama, Dentiscutata cerradensis, Gigaspora decipiens, and AMF's richness were highly correlated with the rhizosphere of M. tenuiflora; and (ii). The rhizosphere of C. madagascariensis was highly correlated with the abundance of Claroideoglomus etunicatum, Rhizoglomus aggregatum, Funneliformis mosseae, and Funneliformis geosporum. The results of our study highlight the importance of considering C. madagascariensis as potential hosts for AMF species from Glomerales, and a potential plant species that increase the bioavailability of exchangeable Na and Ca at semi-arid conditions.
Keywords: biological invasion at the tropics; glomalin; organic acids; root colonization by AMF; sandy soils